Unusual Presentation of Common Disease Is Not Uncommon - Reza, Ishrat Binte; Noor, Nawsabah; Rishad, Mahbub Mayukh; Ahasan, HAM Nazmul; Islam, Quazi Tarikul (Bangladesh Journal of Medicine, 2022)
The commonest site of osseous tuberculosis is the spine. Most vertebral lesions are contiguous. Current research indicates the incidence of multiple level noncontiguous vertebral tuberculosis is 1.1% to 16%1. Here, we describe a case with noncontiguous multisegmental spinal TB with no intervertebral disc involvement. Presentation of noncontiguous multisegmental spinal TB without the involvement of intervertebral disc resembles that of a neoplasm or other spinal infection. Differentiation requires the presence of a combination of general symptoms, laboratory test results, appropriate radiological results, and the physician’s experience. Bangladesh J Medicine 2022; 33: 58-61